What Determines the Size of Public Employment? An Empirical Investigation - Herrera, Santiago; Munoz, Ercio (World Bank, Washington, DC, 2019)
This paper explores the determinants of public employment across the world and finds that it is negatively associated with country size (by population) and positively associated with the income level. The findings show that a country's openness to trade is positively associated with public employment in low- and middle-income countries, but inversely related in high-income countries. The estimated models are used to predict the expected public employment for a country given its income, population, and openness to trade, and to compare the actual levels with the predicted ones. In general, public employment in Latin American countries is below the predicted levels, except for Argentina, Brazil, Ecuador, Mexico, Suriname, Trinidad and Tobago, and the República Bolivariana de Venezuela. Public employment in the Middle East and North Africa is above the predicted levels, particularly in the Arab Republic of Egypt and the Islamic Republic of Iran. East Asian and Pacific countries' public employment is significantly below the predicted levels, particularly in Hong Kong SAR, China; Japan; the Republic of Korea; and Mongolia. Countries in Europe and Central Asia show higher than predicted public employment, mostly in Romania, Denmark, Sweden, Armenia, and Belorussia. Public employment in Sub-Saharan Africa appears to be below the predicted levels, with the notable exceptions of Botswana and South Africa. The deviations from predicted levels are positively correlated with the union density rate, which is negatively associated with private employment rates. Finally, the study finds no statistical association between public and private employment, suggesting the absence of crowding-out in the employment levels.